2021
DOI: 10.22159/ijpps.2021v13i2.39179
|View full text |Cite
|
Sign up to set email alerts
|

Development of Quality Indicators for Pharmaceutical Care Performance Assessment in Nigerian Community Pharmacies: A Delphi Panel

Abstract: Objective: This study aimed to develop quality indicators for assessing pharmaceutical care performance in the Nigerian community pharmacies. Methods: We searched for existing quality indicators through an extensive literature review. The identified quality indicators consisted of thirty-four items in 10 core components. The Delphi method was used to arrive at a consensus on quality indicators for assessing pharmaceutical care performance in the Nigerian community pharmacies by surveying a panel of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“… 45 46 49 52 59 83 113 Of the remaining studies, four each were from Japan, 57 61 62 79 the Netherlands 55 102–104 and Thailand 67 69 95 105 ; three each from Germany, 58 75 108 Estonia, 71 78 115 Iran 48 76 84 and Vietnam 93 96 97 and two each were from Lebanon, 112 114 UAE, 60 86 Brazil 107 110 and Spain. 63 73 One each from Canada, 74 Finland, 99 New Zealand, 43 Lithuania, 44 Malaysia, 87 Poland, 91 Slovenia, 80 Serbia, 70 Sudan, 94 Nigeria, 109 Iraq, 92 Pakistan 89 and China. 85 One study involved five European countries (Denmark, Germany, Netherlands, Poland and Great Britain) to validate a pan-European questionnaire.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 45 46 49 52 59 83 113 Of the remaining studies, four each were from Japan, 57 61 62 79 the Netherlands 55 102–104 and Thailand 67 69 95 105 ; three each from Germany, 58 75 108 Estonia, 71 78 115 Iran 48 76 84 and Vietnam 93 96 97 and two each were from Lebanon, 112 114 UAE, 60 86 Brazil 107 110 and Spain. 63 73 One each from Canada, 74 Finland, 99 New Zealand, 43 Lithuania, 44 Malaysia, 87 Poland, 91 Slovenia, 80 Serbia, 70 Sudan, 94 Nigeria, 109 Iraq, 92 Pakistan 89 and China. 85 One study involved five European countries (Denmark, Germany, Netherlands, Poland and Great Britain) to validate a pan-European questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported the development or assessment of quality indicators for CPs. [99][100][101][102][103][104][105][106][107][108][109][110][111] Four studies described and defined standards or guidelines for good pharmacy practice which can be used to help define quality. [112][113][114][115] Multiple methods were used including: surveys (n=46), 26 114 115 qualitative interviews (n=9), 15 30 45 49 61 69 70 73 83 focus groups, 27 53 63 77 premeasurement and postmeasurement of adherence to standards, 113 biographic and photographic techniques, 42 participant observations, 51 nominal group technique, 43 applying indicators in practice, 103 104 Q-methodology, 96 97 stakeholder event, 112 deductive content analysis, 71 patient stories 65 and mixed methods (n=4).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Strategies should be responsive to changing circumstances and updated accordingly to ensure ongoing effectiveness in enhancing medication quality control and safeguarding public health. By prioritizing implementation strategies, establishing clear timelines and responsibilities, and implementing robust monitoring and evaluation mechanisms, Nigeria can make significant strides in enhancing medication quality control and improving public health outcomes (NNEOMA, and OBINNA, 2021;Conway, et al, 2013).…”
Section: Evaluation and Monitoringmentioning
confidence: 99%